PROTECTION OF WOMEN’S REPRODUCTIVE HEALTH RIGHTS BASED ON INTERNATIONAL LAW AND REGULATION ON LAWS IN INDONESIA - Laila Nurlatifah (Lampung Journal of International Law, 2020)
Women’s health is one of the 12 critical issues stipulated in the Declaration and Action Plan of the Fourth International Conference on Women in Beijing in 1995 until now the issue of reproductive health in Indonesia women are still the main study given the high mortality rate of women caused by disorders of the reproductive organs. This research focuses on the Protection of Women’s Reproductive Health Rights Under International Law and Legislation in Indonesia. This type of research used in this study is normative legal research sourced from primary, secondary, and tertiary legal material whose data collection is carried out by library study techniques. The results of the study indicate two things: (1) Protection of women’s reproductive health rights in international law is found in International Covenant on Civil and Political Rights; International Covenant on Economic, Social and Cultural Rights; Convention on the Elimination of All Forms of Discrimination Against Women and the International Labor Organization (ILO Convention). Action plans for women’s reproductive health rights include the Fourth World Conference on Women Beijing; International Conference on Population and Development Cairo; Sustainable Development Goals or SDGs. (2) Protection of women’s reproductive health rights in legislation in Indonesia is regulated in; The Indonesia Constitution; Law Number 39 Year 2009; Law Number 39 Year 1999; Law No. 13/2003; Law Number 35 of 2014. National policies related to reproductive rights include Government Regulation Number 61 of 2014; Regulation of the Minister of Health of the Republic of Indonesia include Lampung Province Regional Regulation.